Three aspects of Kantian Autonomy: Independence, Self-Determination and Citizenship - Thorpe, Lucas; Demirli, Sun (Con-Textos Kantianos. International Journal of Philosophy, 2024)
In the Groundwork, we find three distinct conceptions of freedom: (i) A negative conception of freedom, understood as a capacity for spontaneous action independent of alien causes; (ii) a positive conception of freedom, understood as the capacity of giving law to oneself; and (iii) a second positive conception, understood as the capacity to give laws that bind others as well as oneself. The dominant interpretation of Kant ignores this third conception of freedom and interprets the second conception as a capacity for self-determination or self-governance, which is seen as the most basic and important Kantian conception of autonomy. In this paper, we will focus mainly on explaining the distinction between the second and third conceptions of autonomy and will defend the claim that the third conception is morally the most basic. We will also explain briefly why Kant thinks that having the capacity for citizenship is necessary for having the capacity for self-governance.